An Overview of Digital Audio Steganography. Issue 6 (1st November 2020) - Dutta, Hrishikesh; Das, Rohan Kumar; Nandi, Sukumar; Prasanna, S. R. Mahadeva
Abstract : Steganography deals with concealing of some messages via some media, which in digital domain is made over speech, image, or video. In the current generation, privacy-related matters are of concern to every individual that makes steganography to have an imperative role in real-world applications. Audio signals are used as covers more frequently as compared with the other cover signals; the reason being their larger size so that more information can be concealed in the cover. Moreover, digital audio signals possess higher redundancy and high data transmission rate that make these suitable for used as covers. This work focuses on audio steganography-based approaches that have effectuated attention from different researchers with its applicability to audio and speech signal processing for communicating information. In this work, different techniques, along with their algorithms and principles, useful in this regard are reviewed and a compendium to digital audio steganography is presented. Additionally, a comparative study among the existing approaches has been provided along with a critical review that can help the community to investigate particular approach according to the requirement.